Investigation and Application of Risk Factors of Macrosomia Based on 10,396 Chinese Pregnant Women - Yuan, Xiaosong; Han, Xiaoya; Jia, Chenbo; Long, Wei; Wang, Huiyan; Yu, Bin; Zhou, Jun (Frontiers in Endocrinology, 2022)
Objective: The objective of this study was to examine the association of fetal macrosomia with maternal D-dimer and blood lipids levels, and explore whether D-dimer and blood lipids, either alone or in combination with traditional risk factors at hospital birth, could be used to predict subsequent delivery of macrosomia . Methods: From April 2016 to March 2017, 10396 women with singleton pregnancy giving birth at around 28–41 weeks of gestation were recruited into the present study. D-dimer and blood lipids levels were measured at hospital admission; and data on birth outcomes were obtained from hospital records. Results: Multivariate logistic regression analysis showed that D-dimer, triglyceride and HDL-C levels were significantly associated with risk of macrosomia independent of traditional risk factors (for D-dimer: adjusted OR: 1.33, 95% CI, 1.23-1.43; for triglyceride: adjusted OR: 1.14, 95% CI, 1.05-1.23; for HDL-C: adjusted OR: 0.35, 95% CI, 0.24-0.51, all P < 0.01 ). More importantly, incorporating D-dimer and blood lipids into the traditional model significantly increased the area under curve (AUC) for prediction of macrosomia (0.783 vs. 0.811; P < 0.01). Conclusion: Our study demonstrates that maternal D-dimer, triglyceride and HDL-C levels before hospital birth could be significant and independent risk factors of fetal macrosomia. Therefore, combining of D-dimer and blood lipids levels with traditional risk factors might improve the ability to predict macrosomia in gestational diabetes mellitus and normal pregnancies.